Competition and the Core - Telser, Lester G. (Journal of Political Economy, 1996)
Core theory is a powerful tool to find competitive market-clearing prices. A familiar economic setting shows this, beginning with a single commodity produced using many factors of production and ending with the general case of many outputs and inputs. The analysis describes when the market has a core. When it has no core, there is a least upper bound on the payment each firm that does not participate in a central market must make that serves as an inducement to restore the core. Since each firm can avoid this penalty by trading in the central market, the result is market-clearing prices that can support an efficient equilibrium.